MODEL NON LINIER GARCH (NGARCH) UNTUK MENGESTIMASI NILAI VALUE at RISK (VaR) PADA IHSG - MAHENDRA, I KOMANG TRY BAYU; DHARMAWAN, KOMANG; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 4 No 2 (2015), 2015)
In investment, risk measurement is important. One of risk measure is Value at Risk (VaR). There are many methods that can be used to estimate risk based on VaR framework. One of them Non Linier GARCH (NGARCH) model. In this research, determination of VaR used NGARCH model. NGARCH model allowed for asymetric behaviour in the volatility such that “good news” or positive return and “bad news” or negative return. Based on calculations of VaR, the higher of the confidence level and the longer the investment period, the risk was greater. Determination of VaR using NGARCH model was less than GARCH model.
Keywords: GARCH model; NGARCH model; Value at Risk